Peningkatan Keterampilan Menceritakan Kembali Teks Biografi Melalui Model Model Think-Pair-Share (TPS) Berbantuan Infografis pada Kelas X SMAN 6 Malang - Suriyanto; Hadi Wardoyo; Jekti Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Biographical text is a subject matter studied by tenth-grade students at the senior high school level. The content of biographical texts is delivered to provide an understanding of the life journeys of inspiring figures, their struggles in achieving their aspirations, as well as the noble values that can be emulated. This study employed a Classroom Action Research (CAR) design with a qualitative approach, conducted over two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 32 tenth-grade students at SMAN 6 Malang in the even semester of the 2025/2026 academic year. The data collected included cycle test results, observational records, interview transcripts, and field notes. The data collection procedures comprised observation, testing, and documentation, while the instructional intervention utilized the Think-Pair-Share (TPS) model consisting of three stages: Think, Pair, and Share. Data analysis followed the interactive model encompassing data reduction, data presentation, and conclusion drawing with verification. The findings revealed that learning mastery based on pretest and Posttest results from 32 students was categorized as moderately active, with pretest mastery increasing from 56.25% in Cycle I to 84.38% in Cycle II, representing a gain of 28.13%, and Posttest mastery increasing from 59.38% in Cycle I to 87.50% in Cycle II, representing a gain of 28.12%. Based on these results, it can be concluded that the Think-Pair-Share (TPS) model assisted by infographics effectively improves the biographical text retelling skills of tenth-grade students at SMAN 6 Malang.